The Influence of Foureye Butterflyfish (Chaetodon capistratus) and Symbiodiniaceae on the Transmission of Stony Coral Tissue Loss Disease - Titus, Kara; O’Connell, Lauren; Matthee, Kristiaan; Childress, Michael (Frontiers in Marine Science, 2022)
Marine diseases have caused large scale decreases in coral cover across the Caribbean and are unfortunately projected to increase as sea surface temperatures rise. Identifying the main drivers of disease transmission is essential for our understanding and response to diseases in the future. This study investigates the effects of direct-contact, waterborne, Symbiodiniaceae composition, and butterflyfish foraging on the transmission rates of stony coral tissue loss disease (SCTLD) across Montastraea cavernosa (MCAV) coral fragments. M. cavernosa fragments were placed in direct contact with diseased Orbicella and Montastraea colonies with the purpose of creating disease MCAV fragments for experimental trials with butterflyfish. Three treatments were used to investigate waterborne transmission (control), mechanically injury to a healthy coral (limited), and direct contact feeding across a diseased and healthy coral (unlimited). After the experimental trials, the composition of Symbiodiniaceae was analyzed for every MCAV fragment. Direct contact transmission took on average 3.9 days in 2019 and 11.9 days in 2020 with significantly quicker rates of transmission between donor diseased Orbicella and Montastraea than Montastraea to Montastraea. The composition of Symbiodiniaceae differed significantly between the fragments used in 2019 (dominated by Durusdinium) than in 2020 (dominated by Cladocopium spp.). The limited treatment had the quickest time to transmission compared to the unlimited and control treatments. Symbiodiniaceae differences between 2019 and 2020 might explain differences in transmission rates and overall susceptibility between the years. The species of Symbiodiniaceae may play a role in the susceptibility of corals to the transmission of SCTLD. Additionally, we also have some suggestive evidence that butterflyfish do not directly increase infection rates, but instead might be increasing infection recovery.